Coblation tonsillectomy versus cold dissection tonsillectomy (Journal of Fatima Jinnah Medical University, 2020)
Post tonsillectomy pain and haemorrhage are important factors for the safety and efficacy of any surgical procedure. This study aimed to compare the efficacy of two surgical techniques i.e. coblator assisted tonsillectomy and time-tested gold standard operation of cold steel dissection tonsillectomy. Assessment of efficacy of coblator assisted tonsillectomy with cold steel dissection tonsillectomy. Patients and Methods: A prospective comparative interventional study was conducted on 100 patients. Coblation group included 50 patients while 50 patients were in cold dissection group. Following parameters like operative time, intraoperative bleeding amount, postoperative bleeding (secondary haemorrhage), postoperative pain, tonsillar fossa healing and time required to resume normal diet were compared. Results: In this study operation with coblator took shorter time with less per operative bleeding (p-value
Keywords: Coblation tonsillectomy; cold dissection tonsillectomy; radio frequency